Awareness of oral cancer and its risk factors in a rural community in Mandya, Karnataka, India - K., Vishma B.; K., Shashikantha S.; P., Sheethal M.; Muniyal, Arpan Singh (International Journal Of Community Medicine And Public Health, 2017)
Background: Oral cancer is a major public health problem faced by mankind today. In India, because of cultural, ethnic, geographic factors and the popularity of addictive habits, the frequency of oral cancer is very high. Thus the present study was undertaken with the objective to determine the level of awareness of oral cancer and the associated risk factors among the general population in a rural community. Methods:The cross sectional study was done among the subjects in 3 villages selected randomly from each primary health centre area covering a sample size of 479 in assessing their knowledge regarding oral cancer. Results: More than one third of the respondents believed that oral cancer is preventable, 41.8% opined that oral cancer can be treated, 18.6% said that oral cancer is contagious and 35.1% opined that the risk of oral cancer increased with age. More than half of the study subjects in 16 -30 years age group knew that oral cancer is preventable and treatable. Nearly 40% of the respondents in the present study did not know the symptoms of oral cancer. Only 16.1% of the respondents had got their oral cavity examined during the past 6 months and 7.7% had undergone screening for oral cancer. Conclusions:Our study found that the level of awareness among the subjects regarding oral cancer and its risk factors was poor.